Prasugrel - Darius, H (Hämostaseologie, 2012)
The antithrombotic therapy in patients with atherosclerotic vascular disease is subject of several new therapeutic approaches. Simultaneous treatment with aspirin and a thienopyridin (clopidogrel) represents the standard of care for patients with acute coronary syndrome and following coronary stenting recommended by many guidelines. Without true evidence this drug combination is used for the prevention of arterial thrombosis in many other vascular interventions (e.g. carotid stenting, aortic stenting, peripherial arterial stents). The main problems of dual antiplatelet therapy with aspirin and clopidogrel are the slow onset of action and the high interindividual variation in the degree of platelet inhibition. The thienopyridin prasugrel is a more potent platelet inhibitor with a more rapid onset of action and smaller interindividual variations in platelet inhibition. The therapeutic superiority of prasugrel with respect to coronary events and stent thromboses was proven in patients with acute coronary syndrome undergoing coronary interventions. Specifically patients with Diabetes mellitus and patients with ST-elevation myocardial infarction seemed to benefit most due to the improved inhibition of platelet activity. A higher rate of bleeding complications was seen in those over the age of 75 years and a body weight below 60 kg for which a daily dose of 5mg/day was approved. Further clinical studies with prasugrel in patients with non-invasively treated acute coronary syndromes are ongoing.